Application value of FRAX in high-altitude areas in China: a systematic review and meta-analysis - Guo, Yong; Zhang, Ying; Jiao, Ting-Ting (Frontiers in Endocrinology, 2026)
BackgroundHigh-altitude environments in China are associated with altered bone metabolism and an increased risk of osteoporotic fractures. Given the limited availability of dual-energy X-ray absorptiometry (DXA) in these regions, the FRAX tool provides a practical alternative for fracture risk assessment. However, the screening performance and diagnostic performance of FRAX in plateau populations remain unclear. This study systematically evaluated the diagnostic accuracy of FRAX—probability of major osteoporotic fracture (PMOF), probability of hip fracture (PHF), and FRAX high-risk thresholds—in high-altitude areas in China.MethodsSix English and Chinese databases were searched from inception to December 31, 2025. Studies reporting true-positive, false-positive, false-negative, and true-negative values for FRAX in populations residing above 1,500 m were included. Pooled sensitivity, specificity, likelihood ratios, diagnostic odds ratio (DOR), and area under the summary receiver operating characteristic (SROC) curve (AUC) were calculated using random-effects models. Heterogeneity was explored through meta-regression and subgroup analyses based on region, bone mineral density (BMD) inclusion, reference standard, gender, and study design. Sensitivity analyses excluding studies with high or unclear Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) risk were performed.ResultsEleven studies were included. For PMOF, the pooled sensitivity and specificity were 0.70 and 0.82, respectively (AUC = 0.82), while PHF yielded pooled estimates of 0.68 and 0.84, respectively (AUC = 0.82). Both analyses showed substantial heterogeneity (I2 > 90%). Subgroup analyses indicated higher specificity in Qinghai–Tibet Plateau populations and mixed-gender cohorts. Meta-regression identified region, BMD inclusion, reference standard, and gender as contributors to heterogeneity. Sensitivity analyses excluding lower-quality studies produced similar estimates. Only three studies evaluated the FRAX high-risk threshold, and the extremely wide confidence intervals—particularly for specificity (95% CI: 0.32–0.98)—indicated marked imprecision.ConclusionsFRAX may provide preliminary and exploratory information for fracture risk screening in high-altitude settings; however, the evidence remains limited and imprecise, precluding firm conclusions regarding its clinical usefulness.Systematic review registrationhttps://inplasy.com/wp-content/uploads/2025/01/INPLASY-Protocol-7296.pdf, identifier INPLASY202510040.